2012
DOI: 10.1016/j.ihj.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for contrast induced nephropathy: A study among Italian patients

Abstract: Atherosclerosis Percutaneous coronary intervention Coronary angiography a b s t r a c tThis study aimed to make a profile of patients at highest risk of developing contrast induced nephropathy (CIN) in order to take appropriate prevention measures. 591 patients undergoing coronary procedures were divided into two groups: patients with (CIN-group) and without (no-CIN) an increase in creatinine level equal or more than 25% from baseline values within 24e48 h after the coronary procedure. All patients underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
6
23
0
Order By: Relevance
“…[15][16][17] Elevated CRP prior to exposure to CM is a significant and independent predictor of CIN; inflammation is a pro-thrombotic state and elevated levels of inflammatory markers may contribute to increased plasma viscosity and subsequent tubular damage. 10,11 Consequences of administration of contrast medium Our study supports previous findings that people with co-existing diabetes and renal dysfunction are at increased risk of CIN 7,18,19 : all five of our patients who developed CIN had pre-existing CKD. The risk of CIN has been shown to be related to the severity of pre-existing CKD, 20,21 but the exact relationship and the point at which damage is most likely to occur has yet to be determined.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[15][16][17] Elevated CRP prior to exposure to CM is a significant and independent predictor of CIN; inflammation is a pro-thrombotic state and elevated levels of inflammatory markers may contribute to increased plasma viscosity and subsequent tubular damage. 10,11 Consequences of administration of contrast medium Our study supports previous findings that people with co-existing diabetes and renal dysfunction are at increased risk of CIN 7,18,19 : all five of our patients who developed CIN had pre-existing CKD. The risk of CIN has been shown to be related to the severity of pre-existing CKD, 20,21 but the exact relationship and the point at which damage is most likely to occur has yet to be determined.…”
Section: Discussionsupporting
confidence: 89%
“…22,23 Inflammatory markers Elevated levels of inflammatory markers, in particular CRP, prior to administration of CM may play a role in CIN following coronary angiography. 10,11 A recent study involving 423 patients found that 13.5% of patients with CRP >5 mg/dL developed CIN, compared with 6.25% of patients with a lower level of CRP. 24 We found no significant difference in renal function when patients were divided into groups depending on their CRP level at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The rates of CIN vary, depending on the study definitions employed and underlying risk factors, and range from 0.6% to 30% or higher among risk groups. [5][6][7][8] CIN is also associated with increased duration of hospitalisation and early and late mortality.…”
mentioning
confidence: 99%
“…No statistical significant sex difference was observed. In study ofEvola et al (2012) observed that average age was 65.32 ± 12.02 years in no-CIN group and 68.94±11.31 years in CIN group. Male was found 337 (69.3%) patients in no-CIN group and 69 (65.7%) in CIN group.…”
mentioning
confidence: 93%